Heterosexual spread of human immunodeficiency virus in Edinburgh. Issue 6621 (20th February 1988) - France, A J; Skidmore, C A; Robertson, J R; Brettle, R P; Roberts, J J K; Burns, S M; Foster, C A; Inglis, J M; Galloway, W B F; Davidson, S J
Abstract : Heterosexual transmission of human immunodeficiency virus (HIV) was investigated in 123 subjects with no apparent risk factor for infection other than having had heterosexual intercourse with a person who was either infected with HIV or at high risk of being infected with it. Seven subjects were found to be infected with the virus. Risk factors for transmission included being the regular sexual partner of an abuser of intravenous drugs and having a sexual relationship of more than 18 months' duration. Anal intercourse was not a risk factor in the three subjects who admitted to it. There were 41 regular partnerships with abusers of intravenous drugs in which the antibody state and history were fully known for both partners. In these partnerships male to female transmission of the virus occurred in five out of 34 (15%) and female to male in one out of seven. In 30 couples in whom one partner was known to be positive for HIV and an abuser of intravenous drugs four female partners were found to be seropositive at first testing, but there were no new positive results on subsequent serial testing. In six of these 30 couples both partners abused intravenous drugs but the partner who was negative for HIV remained so. Few of the partnerships always practised safe sexual techniques, even after a partner was known to be positive for HIV. Heterosexual transmission of HIV occurred but was incomplete and may be related to the timing of the relationship with the infection.